Enhancer-Promoter Interaction of SELF PRUNING 5G Shapes Photoperiod Adaptation. Issue 4 (10th October 2018) - Zhang, Shuaibin; Jiao, Zhicheng; Liu, Lei; Wang, Ketao; Zhong, Deyi; Li, Shengben; Zhao, Tingting; Xu, Xiangyang; Cui, Xia
Abstract : Loss of an enhancer element in the 3′ untranslated region of SP5G conferred day-length insensitivity to domesticated tomato cultivars and helped the species spread worldwide. Abstract: Tomato ( Solanum lycopersicum ) is a major vegetable fruit grown and consumed worldwide. Modern cultivated tomatoes are derived from their wild relative, Solanum pimpinellifolium, a short-day plant that originated from the Andean region of South America. The molecular underpinnings of the regional adaptation and expansion of domesticated tomato remain largely unclear. In this study, we examined flowering time in wild and cultivated tomatoes under both long-day and short-day conditions. Using quantitative trait locus mapping in a recombinant inbred line population, we identified SELF PRUNING 5G ( SP5G ) as a major locus influencing daylength adaptation in tomato. Genetic diversity analysis revealed that the genomic region harboring SP5G shows signatures of a domestication sweep. We found that a 52-bp sequence within the 3ʹ untranslated region of SP5G is essential for the enhanced expression of this gene, leading to delayed flowering time in tomatoes through a promoter-enhancer interaction that occurs only under long-day conditions. We further demonstrate that the absence of the 52-bp sequence attenuates the promoter-enhancer interaction and reduces SP5G expression in cultivated tomatoes, making their flowering time insensitive to daylength. Our findings demonstrate that cis-regulatory variation at the enhancer region of the SP5G 3ʹ untranslated region confers reduced photoperiodic response in cultivated tomatoes, uncovering a regulatory mechanism that could potentially be used to manipulate flowering time in tomato through novel biotechnological approaches.